Digitised Newspapers - A New Eldorado for Historians?: Reflections on Tools, Methods and Epistemology - Estelle Bunout, Maud Ehrmann, Frédéric Clavert, Estelle Bunout, Maud Ehrmann, Frédéric Clavert (Studies in Digital History and Hermeneutics, 2022)
Digitization technologies applied to historical newspapers have changed the research landscape historians were used to. An Eldorado? Despite unquestionable merits, the new digital affordance of historical newspapers also brings drawbacks and possible pitfalls which need to be carefully assessed.